Safe and Ergonomic M-Shape Carrying Education to Improve Mothers' Knowledge and Attitudes in Banteran Village: Edukasi Menggendong M-Shaped yang Aman dan Ergonomis untuk Meningkatkan Pengetahuan dan Sikap Ibu di Desa Banteran - Muharromah Pratiwi, Hikmi; Nani, Desiyani; Sumarwati, Made; Saryono, Saryono (Universitas Haji Sumatera Utara, 2025)
Background: Car carrying activities are an important part of child care, and this skill is recommended for parents. Carrying M-Shaped is a safe and ergonomic holding practice, and is recommended by a child health professional. However, this holding practice is still not known by many parents in Indonesia, so it is necessary to hold a safe and ergonomic M-Shaped M-Shaped education. Methods: This community service activity provides health education and demonstrations of carrying M-Shaped by using jarik fabrics in 24 mothers with children under five in Bantera Village, Sumbang District which was held in August 2024. Health education with lectures and interactive discussions about the concept of holding safe and ergonomic, including the anatomical position of the baby, the benefits M-Shaped using the fingers. Results: The results of this community service activity show an increase in knowledge of the mother's attitude about carrying a safe and ergonomic M-Shape. The difference in the average score of mothers' knowledge is related to carrying M-Shaped before and after the PKM activity is 4.25. In addition, after PKM activities, the majority of mothers agreed that carrying benefits to mothers and infants (75%), carrying a comfortable position (100%), holding M-Shaped safe for newborns (54.17%) and carrying can be done by fathers (87.5%). Conclusion: Community service activities through health education and carrying practice have been proven to increase the knowledge and attitude of mothers regarding holding safe and ergonomic. This activity can continue to be carried out in the community and can be accompanied by evaluating safe and ergonomic holding practices.